Plasma urotensin II levels in primary Raynaud's phenomenon and systemic sclerosis - Gozel, Nevzat; Karatas, Ahmet; Yardim, Meltem; Kinaci, Mesude Seda; Ulu, Ramazan; Demircan, Fatih; Koca, Suleyman Serdar (Tubitak Scientific & Technological Research Council Turkey, 2017)
Background/aim: The pathogenesis of Raynaud's phenomenon (RP) has not yet been fully elucidated. RP is characterized by exaggerated cold-induced vasoconstriction. Urotensin II (UII) is a potent vasoconstrictor. The aim of the present study was to evaluate plasma UII levels in both primary RP and secondary RP associated with systemic sclerosis (SSc). Materials and methods: Fifteen patients with primary RP, 30 patients with RP secondary to SSc, and 30 healthy controls (HC) were included in the study. Raynaud condition scores (RCS) were determined in the primary RP and SSc groups. Modified Rodnan skin score (MRSS) was determined for the SSc patients. Plasma UII level was analyzed by the ELISA method. Results: When compared to the HC group, plasma UII level was lower in the secondary RP group, but not in the primary RP group. Plasma UII level was not directly related to RCS in either the primary or secondary RP group. Moreover, it was not correlated with MRSS in the secondary RP group. Conclusion: The results of the present study suggest that UII is not associated with primary RP. Its level was lower in the secondary RP (SSc) patients. Therefore, it can be concluded that decreased UII level is related to SSc instead of RP.
Keywords: Urotensin II; Raynaud's phenomenon; systemic sclerosis